2009
DOI: 10.1177/1933719109336623
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Amniotic Infection Upregulates Decidual Cell Vascular Endothelial Growth Factor (VEGF) and Neuropilin–1 and –2 Expression: Implications for Infection-Related Preterm Birth

Abstract: Intra-amniotic infection/inflammation (IAI) is a major cause of preterm birth, but the mechanisms responsible are not well understood. This study investigates the effects of IAI on vascular endothelial growth factor (VEGF) as well as VEGF receptor (Flt1, KDR2) and coreceptor (neuropilin-1 and -2) messenger RNA (mRNA) and protein expression at the maternal-fetal interface, both in vitro and in vivo. Decidual stromal cells (DSCs) were isolated from term placentae, purified, and treated with 10(-8) mol/L estradio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 33 publications
1
32
1
1
Order By: Relevance
“…Together, these results demonstrated that a reduction in inflammation because of increased maternal regulatory cytokines may be beneficial for growth and development of certain fetal organs. For putative organ-specific growth factors, f-VEGF was positively associated with fetal brain, kidney, and lung masses, which contrasts with reports that placental VEGF is associated with preterm birth (58). Our finding that m-VEGF and af-VEFG were negative predictors of fetal mass suggests that f-VEGF may be an organ-specific growth factor.…”
Section: Discussioncontrasting
confidence: 99%
“…Together, these results demonstrated that a reduction in inflammation because of increased maternal regulatory cytokines may be beneficial for growth and development of certain fetal organs. For putative organ-specific growth factors, f-VEGF was positively associated with fetal brain, kidney, and lung masses, which contrasts with reports that placental VEGF is associated with preterm birth (58). Our finding that m-VEGF and af-VEFG were negative predictors of fetal mass suggests that f-VEGF may be an organ-specific growth factor.…”
Section: Discussioncontrasting
confidence: 99%
“…2). Consistent with earlier publications (23,30), IL-1b did not stimulate sFlt-1 production by HTR-8/SV neo cells (Fig. 2F).…”
Section: Functional Effects Of Gnrh-i and -Ii On Trophoblastssupporting
confidence: 93%
“…First-strand complementary DNA (cDNA) was generated by reverse transcription (RT) of 1 mg RNA using p(dT) [12][13][14][15][16][17][18] primers with MMLV-reverse transcriptase (Invitrogen) and amplified as previously described (23,24). The polymerase chain reaction (PCR) products were separated by gel electrophoresis in 1.5% agarose and visualized by ethidium bromide staining on an ultraviolet transilluminator.…”
Section: Reverse-transcription Polymerase Chain Reactionmentioning
confidence: 99%
“…After dissociation, the leukocytes are enriched from the total population of the decidual cells by density gradient centrifugation. Various density gradient media have been previously utilized, the most common of which are Percoll (a suspension of colloidal silica particles) 48 and Ficoll (a polymer of sucrose with a high synthetic molecular weight) 49 . The superior efficiency of isolation by the sucrose polymer has been previously shown 50 , and the protocol described herein further proves that this density gradient media produces a sufficiently high purity of mononuclear leukocytes.…”
Section: Introductionmentioning
confidence: 99%